Body size at birth and age‐related macular degeneration in old age. Issue 5 (29th December 2019) - Haapanen, Markus J.; von Bonsdorff, Mikaela B.; Fisher, Diana; Jonasson, Fridbert; Eiriksdottir, Gudny; Gudnason, Vilmundur; Cotch, Mary Frances
Abstract: Purpose: To study associations between body size at birth and age‐related macular degeneration (AMD) in old age. Methods: The study sample consists of 1497 community‐dwelling individuals (56.1% women) aged 67–89 years with birth data and retinal data collected twice in old age 5 years apart. Birth data (weight, length, birth order) were extracted from original birth records. Digital retinal photographs were graded to determine AMD status. Data on covariates were collected at the baseline physical examination in old age. Multivariable regression analyses were used to study the association between birth data and AMD adjusting for known confounding factors, including birth year cohort effects. Results: The prevalence and 5‐year incidence of any AMD were 33.1% and 17.0%, respectively. Men and women born in 1930–1936 were significantly leaner and slightly longer at birth compared to those in earlier birth cohorts. There were no consistent associations between weight, length or ponderal index (PI) at birth and AMD in old age even when stratified by birth cohort. Age‐related macular degeneration (AMD) prevalence (39.8%) and 5‐year incidence (28.6%) were highest in individuals who were in the highest quartile of PI at birth and who were obese in old age. Conclusion: Body size at birth was not consistently associated with AMD in old age, suggesting that intrauterine growth might have little direct importance in the development of AMD in old age. It is possible that some yet unknown factors related to larger size at birth and obesity in old age may explain differences in the prevalence and incidence of AMD in the ageing population.